Comparison of three anaerobic digestion reactors for low‐carbon wastewater treatment. (31st March 2022) - Wei, Denghui; Zhang, Xiaojing; Chen, Zhao; He, Yu; Dai, Jiaqian; Zhang, Shengnan
Abstract: In this study, three anaerobic digestion reactors using up‐flow anaerobic sludge blanket (UASB), anaerobic sequencing batch reactor (AnSBR), and anaerobic membrane bioreactor (AnMBR) were studied. The chemical oxygen demand (COD), gas production, sludge performance, and microbial characteristics of the anaerobic digestion process were assessed. The results showed that the average COD removal efficiencies reached 86%, 83%, and 85%, with corresponding removed rates of 2.49, 0.48, and 0.79 kg COD m −3 d −1 in UASB, AnSBR, and AnMBR, respectively. After the reactors attained stable operation, both extracellular polymeric substances and soluble microbial products decreased in all the reactors compared with the seed sludge. Methanothrix was the dominant archaea for methane production in the UASB, the relative abundance of which increased from 58.3% to 83.4%. These results identify UASB as the most suitable reactor for anaerobic digestion when treating wastewater with low carbon. Such reactors are important for the application and development of the energy self‐sufficiency in sewage treatment. Practitioner Points: UASB, SBR, and MBR were adopted to treat low‐carbon wastewater using anaerobic digestion process. UASB performed the highest COD removal from low‐carbon wastewater. The main microorganisms in UASB were Methanothrix, Methanomassiliicoccus, and Methanobacterium . Abstract : UASB was feasible for treating low‐organic wastewater.